Strategi Pembelajaran Model Berdiferensiasi Dalam Meningkatkan Minat Bealajar Siswa Pada Mata Pelajaran PAI - Syifa Nashri Khoiriyah1; Yufi Nasrullah; asep tutun usman; masripah (Advances In Education Journal, 2025)
Students' diverse learning interests require instructional strategies that accommodate these differences. Differentiated instruction is an approach that enables teachers to tailor the teaching and learning process according to students’ needs, interests, and learning styles. This study aims to analyze the effectiveness of differentiated learning strategies in increasing students’ interest in Islamic Religious Education (IRE). A descriptive qualitative method was used, with data collected through observation and teacher interviews. The results show that implementing this model enhances student engagement, provides more meaningful learning experiences, and increases interest in understanding IRE material. The success of this strategy is supported by adjusting content, process, and product based on students' readiness and interests. Therefore, differentiated instruction proves effective in boosting students’ learning interest, and teachers need to strengthen their skills in designing differentiated lessons to better accommodate students’ learning needs.